Developing a Digital Community of Practice to address professional isolation among emergency nurses in Lesotho - Mahlomola Kutoane; Tricia Scott; Petra Brysiewicz (International Journal of Africa Nursing Sciences)
Introduction: Professional isolation is a deficiency in one’s network of professional relations and is associated with compromised health service delivery and quality of life among health professionals, working in low-resource environments. Aim: This paper describes the design process undertaken to develop a Digital Community of Practice (DCOP) to address professional isolation among emergency nurses in Lesotho. Method: This study is part of a larger, four-cycle collaborative action research project aimed at developing an intervention to manage professional isolation among emergency nurses in low-resource environments. Guided by the Communities of Practice Model’s five-phased life cycle, a Digital Community of Practice was developed. In Cycle One, a needs assessment was conducted through a scoping review and five focus group discussions. Cycle Two involved 13 individual interviews to explore perceptions of professional isolation. In Cycle Three, the research team concluded that a Digital Community of Practice could effectively manage professional isolation among emergency nurses in Lesotho. Results: The preliminary results from the evaluation of the implementation of a digital community of practice show that it was functional, highlighting mutual engagement, joint enterprise, and a shared repertoire. These results show how a digital community of practice enabled Emergency Nurses to gradually implement a change in practice; as well as to recognize and minimize professional isolation among themselves. Conclusion: Combining results from Cycles One and Two, the research team developed and implemented a Digital Community of Practice. The results show that a Digital Community of Practice using WhatsApp may be a useful intervention strategy for managing professional isolation with emergency nurses in marginalised areas.